2015
DOI: 10.1007/s12010-015-1642-y
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Agents Simultaneously Improving the Production and Antioxidant Activity of Polyphenols from Inonotus obliquus by Submerged Fermentation

Abstract: Polyphenols are important secondary metabolites from the edible and medicinal mushroom Inonotus obliquus. Both the rarity of I. obliquus fruit body and the low efficiency of current method of submerged fermentation lead to a low yield of polyphenols. This study was aimed to determine the effect of applying stimulatory agents to liquid cultured I. obliquus on the simultaneous accumulation of exo-polyphenols (EPC) and endo-polyphenols (IPC). Linoleic acid was the most effective out of the 17 tested stimulatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…fungal mycelia is widely produced in SSF using substrates such as grains, sawdust or wood from different plant species (Yang and Liau, 1998). Nevertheless, it has been reported that SCF improves potential advantage than SSF, because inoculums can be uniformly dispersed in the substrate, and the time and/or harvest speed are reduced (Yang and Liau, 1998;Xu and Zhu, 2011;Xu et al, 2015). Moreover, fungal mycelia production during the fermentation process varies extensively, depending on the species of fungus and environmental or culture conditions used (temperature, initial pH, surface-aeration, aeration rate, rotating speed, and stimulatory agents, among others), which consequently affect phytochemical extraction from the substrate (Yang and Liau, 1998;Xu and Zhu, 2011;Xu et al, 2015).…”
Section: Fungal Culture Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…fungal mycelia is widely produced in SSF using substrates such as grains, sawdust or wood from different plant species (Yang and Liau, 1998). Nevertheless, it has been reported that SCF improves potential advantage than SSF, because inoculums can be uniformly dispersed in the substrate, and the time and/or harvest speed are reduced (Yang and Liau, 1998;Xu and Zhu, 2011;Xu et al, 2015). Moreover, fungal mycelia production during the fermentation process varies extensively, depending on the species of fungus and environmental or culture conditions used (temperature, initial pH, surface-aeration, aeration rate, rotating speed, and stimulatory agents, among others), which consequently affect phytochemical extraction from the substrate (Yang and Liau, 1998;Xu and Zhu, 2011;Xu et al, 2015).…”
Section: Fungal Culture Fermentationmentioning
confidence: 99%
“…In relation to the aforementioned, the use of agro-in-dustrial by-products as substrates in combination with fungal fermentation-assisted extraction (SSF and SCF), are considered an alternative method for the extraction of phytochemicals, including triterpenoids, polysaccharides, and phenolic compounds, which could be obtained through agro-industrial by-products (Xu and Zhu, 2011;Xu et al, 2014;Xu et al, 2015;Dey et al, 2016).…”
Section: Phenolic Compounds Extraction By Fungal Fermentationmentioning
confidence: 99%
“…Meanwhile, supplementing Ag + , Cu 2+ and Ca 2+ could stimulate accumulation of lanosterol and ergosterol (Zheng et al, 2008a). Adding methyl jasmonate or linoleic acid could enhance more than 50 % of the total triterpenoid production as well as its phenolic content and diversity (Xu et al, 2015b;Xu et al, 2016a). Besides, cultivating the mycelium with the aqueous extracts or methanolic extracts of birch bark, birch core or chitosan could significantly enhance the steroid production of inotodiol, ergosterol peroxide, betulin, ergosterol, cholesterol, lanosterol, stigmasterol, and sitosterol (Kahlos, 1994;Wang et al, 2014).…”
Section: Terpenoidsmentioning
confidence: 99%
“…For example, instead of using lignocellu-losic medium during submerged cultures, the coculture of chaga with other white-rot fungi such as Phellinus punctatus or Phellinus morii leads to an increased accumulation of phenolic compounds including phelligridin C, phelligridin H, methyl inoscavin A, inoscavin C, inoscavin B, davallialactone, methyl davallialactone, as well as melanins and various lanostane-type triterpenoids, even though production of mycelial biomass will be inhibited (Zheng et al, 2011c). Furthermore, imposing oxidative stress by moderately supplementing with H 2 O 2 or Na 2 [Fe(CN) 5 NO] (sodium nitroprusside), or using other stimulatory agents such as γ-irradiation, Tween-20, Tween-80, jasmonic acid, L-tyrosine, linoleic acid, heavy metal ions (Mg 2+ , Cu 2+ , Co 2+ , Zn 2+ , and Mn 2+ ) and extracts or cell debris of Alternaria alternata, Aspergillus flavus and Mucor racemosus in mycelia medium of chaga can also significantly increase the production, accumulation and/or diversity of phenolics, and corresponding antioxidant ability of extracts thereof Poyedinok et al, 2020;Xu et al, 2015a;Xu et al, 2015b;Xu et al, 2019b;Xu et al, 2016b;Yang and Zheng, 1994;Zhao et al, 2009;Zheng et al, 2007b;Zheng et al, 2009a;Zheng et al, 2009b). More insights into the regulatory machinery that controls biosynthesis of chaga phenolics, especially styrylpyrones, are discussed below.…”
Section: Bioactive Compounds and Bioactive Properties Of Chagamentioning
confidence: 99%
“…Studies have found that the addition of betulin as a stimulating factor to the fermentation medium of Inonotus obliquus can significantly increase the levels of metabolites such as triterpenoids and steroids [17]. Some studies have found that adding birch extract to the culture medium by water extraction can significantly promote the mycelia growth of Inonotus obliquus and the steroid content [18,19,20]. The nutrients of birch extract, which mainly contains fatty acids, polyphenols, triterpenoids, betulin and betulinic acid were studied by HPLC and GC-MS [19,21].…”
Section: Introductionmentioning
confidence: 99%